Peningkatan Kadar Troponin-I Paska Resusitasi Cairan pada Sus Scrofa Sebagai Model Hewan Coba Renjatan - Hotber E. R. Pasaribu; Antonius H Pudjiadi; Rismala Dewi (Fakultas Kedokteran Universitas Riau, 2018)
Provision large amounts of fluids in a short period is known can cause hypervolemia. Therefore, an examination is needed to find out that the fluid resuscitation being administered does not cause hypervolemia. The purpose of this study is to assess the effect of hypervolemic resuscitation on cardiac contractility. The study was conducted on 10 male Sus Scrofa aged 6-8 weeks, as shocked animal models. There are 3 types of resuscitation treatments : normovolemic, hypervolemic-1, and hypervolemic-2. Cardiac contractility was assessed using DPmax and troponin-i levels. There was an increase in troponin-i levels after hypervolemic fluid resuscitation (p = 0.05). There is a decrease in cardiac contractility after hypervolemic resuscitation. Decreased cardiac contractility is associated with increased troponin-i (r = 0.720; p = 0.020). Based on the results, we conclude hypervolemic resuscitation causes changes in troponin-i levels, which reflect changes in cardiac contractility.